Employment and labour relations in the Theban necropolis in the Ramesside period - Eyre, C; Eyre, C. J. (1981)
The text deals essentially with the workmen employed on the construction of royal tombs in the Valley of the Kings during the Nineteenth and Twentieth Dynasties in Egypt. Material from other sites and periods is used freely, but only for comparative purposes. Attention is paid, wherever possible, to placing this workforce within the context of Egyptian society as a whole, and to relating their behaviour and events concerning them to general historical developments in Egypt during the Ramesside period. The first chapter contains a survey of the documents preserved from the village of Deir el Medina, where the workmen lived, and from the sites where they worked, with attempts to classify these documents, to discuss their purpose, their use, their authorship, and the light they threw on Egyptian documentary practices in general. The following two chapters discuss the relationship between the workmen and the king, as their employer, as the head of state, and as the object of worship in the workmen's village. Succeeding chapters discuss the relationship between the workmen and the vizier, the high priest of Amon, and the local mayors, with particular attention paid to important individual officials and to changes in these relationships during the course of the period under discussion. Than evidence is collected for a discussion of the way in which workmen were recruited, and so far as possible, of the way they were punished and dismissed. This is followed by a description of the way in which the work on the tombs and the work of local supply and service staff was controlled. The final two chapters contain a collection of references to labour troubles at Deir el Medina during the Twentieth Dynasty, and an attempt to draw wider conclusions from these about the nature of employment on that site.